WORK CHARACTERISTICS, VISUAL AND ENERGY NEEDS IN OFFICE AND FACTORY LIGHTING - Öztürk, Yasemin; Kazanasmaz, Zehra Tuğçe (MATTER: International Journal of Science and Technology, 2018)
The visual effect of lighting effects health and comfort conditions of a working place. Lighting design requirements are based on the function of spaces. Healthy and comfortable work spaces increase user motivation, mentally support them, improve concentration and physically decrease accidents. Lighting strategies applied to the offices are arranged according to working hours and needs of the user, while they are needed to be implemented more systematically in factories than the offices due to the industrial characterization including task types, machines/equipment, etc. Working styles influence the lighting strategies. The purpose is to prevent the undesired reflection from the computer screen in offices, while it is essential to provide an environment that decreases the work accidents in industrial buildings. Color rendering index is a vital issue to determine the reality sense of color mostly necessary for reading tasks in offices. Energy requirements can be lower by LED technologies in factories and by auto controlled systems in the open plan offices to apply appropriate daylighting plan. So, working time, working style, color rendering index and energy benefits are discussed regarding two workspaces, offices and factories, comparatively. Such a comparison can contribute to literature in terms of indicating key design considerations in two distinctive work spaces.